Examining Qanun in Aceh from a human rights perspective: status, substance and impact on vulnerable groups and minorities - Dian Andi Nur Aziz; Al Khanif; Mimin Dwi Hartono; Ade Angelia Yusniar Marbun (State Islamic University of Salatiga, 2023)
The Helsinki Agreement between the Aceh Freedom Movement (GAM) and the Indonesian Government aimed to end long-standing conflict and inequality in Aceh. It also legally empowered the Acehnese to govern their own province and protect their citizens from human rights abuses. Regrettably, the implementation of laws and policies in Aceh since the agreement, such as Qanun, has had an adverse effect on human rights, particularly for vulnerable groups and minorities. This paper analyses the need to align the substance of Qanun with international human rights norms and assesses the feasibility of implementing Qanun without violating human rights. The research method used is the qualitative method. The data collection technique mainly involves in-depth interviews with key informants, including academics, members of Aceh parliament, civil society organisations, representatives of religious organisations, the Aceh Sharia Court, the Acehnese government, and practitioners on women and children, as well as victims of human rights violations and literature reviews. This study has found that the implementation of Aceh Qanun has had negative consequences on the protection of human rights, particularly for vulnerable groups and minorities. In addition, it also affects vulnerable groups, Muslim and non-Muslim minorities who have been “forced to conform” with Aceh Qanun. The paper advocates for a harmonious balance between Qanun and human rights, which can be achieved through a more constructive dialogue between the two.